UPLC SEPARATION ANALYSIS OF EMTRICITABINE, TENOFOVIR, COBICISTAT AND ELVITEGRAVIR FROM THEIR DEGRADATION PRODUCTS - P., Revathi Naga Lakshmi; P., Prahlad; S. K., Mastanamma; N., Ravindra; Rao M., Venkata Basaveswara (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: A simple, rapid, accurate and precise stability-indicating UPLC analytical method has been developed and validated for the quantitative analysis of Emtricitabine, Tenofovir, Cobicistat and Elvitegravir in bulk drugs and combined dosage forms. Methods: ACE C18 (50 mm x 3 mm, 2µ). The column temperature was maintained at 30oC and run time 8 min. The mobile phase was a mixture of Mobile Phase: A–0.1% TFA in Acetonitrile, B–0.1% TFA in Milli-Q-water. The injection volume of samples was 20μl. UV detection was carried out using a UV-PDA detector at 240 nm. The validation of this method was done as per ICH guidelines. Results: The retention times were observed as 1.46, 3.59, 4.13, 4.64 min for Emtricitabine, Tenofovir disoproxyl fumarate, Cobicistat, and Elvitegravir respectively. Linearity ranges were observed 150-275 µg/ml Emtricitabine, 250-375 µg/ml Tenofovir, 100-225 µg/ml Cobicistat and 100-225 µg/ml Elvitegravir. Relative Standard Deviation did not exceed 2. Conclusion: The newly developed UPLC method for separation of different degradation products along with the pure drugs were found to be capable of giving faster retention times while still maintaining good resolution than that achieved with conventional HPLC. The decreased flow rate 0.4 ml/min, in UPLC indicate more economical. This method exhibited an excellent performance in terms of sensitivity and speed. The results of stress testing undertaken according to the ICH guidelines reveal that the method is specific and stability-indicating. The proposed method has the ability to separate these drugs from their degradation products in tablet dosage forms and hence can be applied to the analysis of routine quality control samples and samples obtained from stability studies. Keywords: Stability indicating assay, RP-UPLC, Emtricitabine, Tenofovir, Cobicistat, Elvitegravir, Forced degradation studies